LAPISAN PEMAHAMAN KONSEP MATEMATIKA DALAM MENYELESAIKAN SOAL TIMSS BAGI SISWA SMP KELAS VIII - Antika Muning Dewi Cahyati; Kriswandani Kriswandani (INSPIRAMATIKA, 2017)
This qualitative descriptive paper aims to describe layers of conceptual understanding in mathematic for completing TIMSS questions designed for 8th grader students in SMP Negeri 02 Banyubiru Kabupaten Semarang. The understanding level includes 8 points which are Primitive Knowing (Pk), Image Making (Im), Image Having (Ih), Property Noticing (Pn), Formalising (F), Observing (O), Structuring (S), and Inventising (Iv). Five 8th grader students in SMP Negeri 02 Banyubiru consisted as the sample and it was chosen by purposive sampling. The data for the study were collected through task and interview. The writer utilized data reduction, data presentation and conclusion electing to analyze the data. Result showed that: 1) for solving TIMSS questions about natures of geometry regarding angle and geometric shapes, 80% of the participants use F layer, whereas the other 20% use Ih layer. 2) for solving TIMSS questions about equivalence and congruence, 60% of the participants use Iv layer, and the other 40% use O layer. 3) for solving TIMSS questions about relation between two-dimensional and three dimensional figures, 80% of the participants use Iv layers, and the other 20% use Pn layers. 4) For solving TIMSS questions utilizing the appropriate measurement formula to find the length of sides, circumference, area, surface area, and volume, 100% of the participants use Iv layer.